The development of the Deployment Resilience Seminar - Van Breda, Adrian Du Plessis (Department of Social Development, 2023)
A primary stressor in the South African Navy is the routine deployment of men to sea. This requires repeated adjustments of the family system, decreasing family well-being, which in turn decreases the morale, productivity and retention of sailors. This dissertation describes and critiques the process of developing an occupational social work intervention to assist families in resisting the stress of deployments, that is, to increase their 'deployment resilience. The study began with four years of problem analysis, comprising an analysis of clinical work, a literature review, a sample survey of the experience of sailors and their wives of naval deployments, an investigation of factors associated with effective coping and a social survey of naval employees. The resultant data were reviewed and seven factors associated with deployment resilience were identified and operationalized. These factors included emotional containment, presence of social supports, financial preparedness, adjustment of children, a 'husband-aware' family structure, a secure and progressive marital relationship and positive attitudes towards the navy and deployments. A one day seminar to enhance these seven factors was designed, the process of which is described. The first complete trial implementation of the Deployment Resilience Seminar is described and evaluated. The seminar was attended by 34 individuals, representing 18 couples, from one of the Navy's ships. The implementation was, on the whole, successful, although some changes were required. The seminar was rated as helpful by subjects, who completed a seminar evaluation immediately after the seminar and two months thereafter. Pre-seminar and post-seminar assessments of participants were conducted at a two month interval using three scales: the Heimler Scale of Social Functioning, the Family Assessment Device and the Deployment Resilience Scale (being developed by the author). T-tests of the 24 participants who returned both sets of questionnaires indicate that the seminar was successful in enhancing the social and family functioning and deployment resilience of participants. Participants who actively implemented changes based on the seminar evidenced substantially greater improvements than those who did not. Implications of the seminar for military and civilian communities and areas requiring ongoing design and development are discussed. Recommendations to naval management to reduce the risk of deployment stress are suggested. The views expressed in this work are those of the author alone and not those of the South African Medical Services, the South African National Defence Force or any other organization.